Development of Interactive Formative Assessment Based on Gimkit for Human Digestive System Material for Fifth Grade Elementary School Students - Safiera Putri Ramadhania Nasution; Nino Indrianto (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
The rapid development of information technology in the era of the Fourth Industrial Revolution has influenced various aspects of education, including assessment practices. However, the implementation of interactive formative assessment in elementary science learning remains limited and is still dominated by conventional written tests. This study aims to develop a Gimkit-based formative assessment tool for fifth-grade science learning on the topic of the human digestive system. This study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. The developed product is a formative assessment implemented through the Gimkit application using the Snowbrawl game mode. It consists of 10 multiple-choice and image-based questions designed to measure both Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS). The visual components include illustrative images of digestive organs and an interactive game-based layout to enhance student engagement. Data were collected through observations, questionnaires, and documentation, and were analyzed using descriptive qualitative and quantitative techniques. The results of expert validation conducted by material experts, media experts, and the classroom teacher showed an average validity score of 85.72%, which was categorized as highly valid. Meanwhile, the practicality test involving students and the teacher obtained an average score of 85.92%, which was categorized as very practical. These findings indicate that the Gimkit-based formative assessment tool developed in this study is valid and practical for use in elementary science learning, particularly for the topic of the human digestive system, and has the potential to support students’ engagement and learning processes.